The auxin signaling pathway to its PIN transporters: insights based on a meta-analysis of auxin-induced transcriptomes - V. V. Kovrizhnykh; Z. S. Mustafin; Z. Z. Bagautdinova (Вавиловский журнал генетики и селекции)
Active polar transport of the plant hormone auxin carried out by its PIN transporters is a key link in the formation and maintenance of auxin distribution, which, in turn, determines plant morphogenesis. The plasticity of auxin distribution is largely realized through the molecular genetic regulation of the expression of its transporters belonging to the PIN-FORMED (PIN) protein family. Regulation of auxin-response genes occurs through the ARF-Aux/IAA signaling pathway. However, it is not known which ARF-Aux/IAA proteins are involved in the regulation of PIN gene expression by auxin. In Arabidopsis thaliana, the PIN, ARF, and Aux/IAA families contain a larger number of members; their various combinations are possible in realization of the signaling pathway, and this is a challenge for understanding the mechanisms of this process. The use of high-throughput sequencing data on auxin-induced transcriptomes makes it possible to identify candidate genes involved in the regulation of PIN expression. To address this problem, we created an approach for the meta-analysis of auxin-induced transcriptomes, which helped us select genes that change their expression during the auxin response together with PIN1, PIN3, PIN4 and PIN7. Possible regulators of ARF-Aux/IAA signaling pathway for each of the PINs under study were identif ied, and so were the aspects of their regulatory circuits both common for groups of PIN genes and specif ic for each PIN gene. Reconstruction of gene networks and their analysis predicted possible interactions between genes and served as an additional conf irmation of the pathways obtained in the meta-analysis. The approach developed can be used in the search for gene expression regulators in other genomewide data.